The cross-section of mutual fund fee dispersion - Iannotta, Giuliano; Navone, Marco (Journal of Banking & Finance, 2012)
In this paper, we empirically analyze the factors affecting the cross section of mutual fund fee dispersion. In the context of equity mutual funds, fee dispersion stems primarily from the heterogeneity of products, clienteles and production functions. However, the relevant theory predicts that search costs can also generate fee dispersion. By controlling for observable sources of heterogeneity, we find that fee dispersion decreases with fund size and age, as well as with the amount of assets under management of the investment company. In addition, we find lower levels of fee dispersion for funds that charge marketing and distribution fees. Although we cannot rule out the possibility that these factors are a proxy for some unobserved source of heterogeneity, our results are also consistent with the theoretical prediction that search costs positively affect fee dispersion.